Popular autonomy and democratic socialism in Rosa Luxemburg's political thougth - Rotolo, Tatiana Macedo Soares (Cadernos de Ética e Filosofia Política, 2006)
This work aims to approach Rosa Luxemburg's thought from the fundamental idea that sustains her entire political conception: the notion that the active participation of the masses in the foundation of any political process is essential to the revolutionary process. This idea leads to an understanding of Rosa Luxemburg's political advocations such as the acquisition of popular autonomy. It is also the center of her ideas about a model of democratic socialism, pervading her entire work and exerting its effect on the current political dynamics of many movements and sectors of the contemporary left.